Determination of kinetic parameters for biomass combustion. (September 2016) - Álvarez, A.; Pizarro, C.; García, R.; Bueno, J.L.; Lavín, A.G.
Highlights: Kinetic parameters of 28 biomass samples were experimentally determined. Model-free method Coats–Redfern was used. Numerical solution of derivative kinetic equation was obtained. A two-stage reaction mechanism was proposed. Abstract: The aim of this work is to provide a wide database of kinetic data for the most common biomass by thermogravimetric analysis (TGA) and differential thermogravimetry (DTG). Due to the characteristic parameters of DTG curves, a two-stage reaction model is proposed and the kinetic parameters obtained from model-based methods with energy activation values for first and second stages in the range 1.75 · 10 4 –1.55 · 10 5  J/mol and 1.62 · 10 4 –2.37 · 10 5  J/mol, respectively. However, it has been found that Flynn–Wall–Ozawa and Kissinger–Akahira–Sunose model-free methods are not suitable to determine the kinetic parameters of biomass combustion since the assumptions of these two methods were not accomplished in the full range of the combustion process.